Umbrella summer - Graff, Lisa (Lisa Colleen), 1981- (Laura Geringer Books, 2009)
After her brother Jared dies, ten-year-old Annie worries about the hidden dangers of everything, from bug bites to bicycle riding, until she is befriended by a new neighbor who is grieving her own loss.